Effect of intensive blood pressure control on subtypes of mild cognitive impairment and risk of progression from SPRINT study. Issue 5 (26th November 2021) - Gaussoin, Sarah A.; Pajewski, Nicholas M.; Chelune, Gordon; Cleveland, Maryjo L.; Crowe, Michael G.; Launer, Lenore J.; Lerner, Alan J.; Martindale‐Adams, Jennifer; Nichols, Linda O.; Ogrocki, Paula K.; Sachs, Bonnie C.; Sink, Kaycee M.; et al.
Abstract: Background: To examine the effect of intensive blood pressure control on the occurrence of subtypes of mild cognitive impairment (MCI) and determine the risk of progression to dementia or death. Methods: Secondary analysis of a randomized trial of community‐dwelling adults (≥50 years) with hypertension. Participants were randomized to a systolic blood pressure (SBP) goal of <120 mm Hg (intensive treatment; n = 4678) or <140 mm Hg (Standard treatment; n = 4683). Outcomes included adjudicated MCI, MCI subtype (amnestic, non‐amnestic, multi‐domain, single domain), and probable dementia. Multistate survival models were used to examine transitions in cognitive status accounting for the competing risk of death. Results: Among 9361 randomized participants (mean age, 67.9 years; 3332 women [35.6%]), 640 participants met the protocol definition for MCI, with intensive treatment reducing the risk of MCI overall (hazard ratio [HR], 0.81 [95% confidence interval CI, 0.69–0.94]), as previously reported. This effect was largely reflected in amnestic subtypes (HR, 0.78 [95% CI, 0.66–0.92]) and multi‐domain subtypes (HR, 0.78 [95% CI, 0.65–0.93]). An adjudication of MCI, as compared with normal cognitive function, substantially increased the probability of progressing to probable dementia (5.9% [95% CI: 4.5%–7.7%] vs. 0.6% [95% CI: 0.3%–0.9%]) and to death (10.0% [95% CI: 8.3%–11.9%] vs. 2.3% [95% CI: 2.0%–2.7%]) within 2 years. Conclusions: Intensive treatment reduced the risk for amnestic and multi‐domain subtypes of MCI. An adjudication of MCI was associated with increased risk of progression to dementia and death, highlighting the relevance of MCI as a primary outcome in clinical and research settings. Abstract : See related Editorial by Deardorff et al . in this issue.